(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Research on the biodiversity of Hemiptera was carried out in 1997- 1999 in two viticultura! areas of Valtellina. The first site in Postalesio is situated in the vicinity of a forest and has a humid microclimate, while the other site in Sassella is located in a simpler environment with a dry microclimate. In both areas two vineyards were selected: one that was full of weeds and a second one without weeds. In the Postalesio area the development of weeds was observed for many years, its composition is diversified and weeding is accurate, while in the Sassella area the growth of weeds is more recent with a more trivial composition. Different biodiversity indexes (Index of Shannon-Weaver H’, the Hill’s numbers: N0, N 1’ D, N2, N inf, Index of Pielou J’) and of similarity (Si:irensen’s index QS) have been applied to the data. On the whole 59 species of Heteroptera were collected belonging to 12 families. The highest number of species and indexes of biodiversity were found in the vineyard in Postalesio with weeds in 1997; the presence of the forest and the diverse flora have favoured the biocenosis of Hemiptera. In the Sassella vineyard with weeds, whose vegetation has become richer during the study, the indices of biodiversity have shown a constant increase from ’97 to ’99. In the same area the flora that has taken over in the weed-free vineyard has led to a biodiversity comparable to the one with weeds during the first year, while after two years the situation worsened. In the other weed-free vineyard no Heteroptera have been found.